PENERAPAN METODE HIRARC PADA LANTAI PRODUKSI DI PERUSAHAAN OTOMOTIF - Andriana, Iyan; Rabbani, Daffa Khairi (Teknik Industri Unikom, 2024)
In 2024, automotive industry players are projected to experience an increase, this will occur in two-wheeled and four-wheeled vehicles. In line with this development, companies are required to always maintain their productivity and comply with the rules in implementing Occupational Health and Safety, the implementation of K3 is a management policy in order to protect workers and the company in the short and long term. Identification of potential hazards and efforts to prevent work accidents in Automotive Company production areas is one way to prevent work accidents. The method used in this research is HIRARC (Hazard Identification, Risk Assessment, and Risk Control), through direct observation procedures, interviews with employees, and analysis of documents related to work safety. In the hazard identification stage, 9 potential hazards were found in traffic accidents, namely operators being hit by finished products, being hit by drums of chemicals on the Tank line, being scratched by cutting tools on the cutting line, being rolled up by rolls of foam on the Foaming line, fires, the risk of exposure to noise on the HR-line. 2, exposed to fire in the Flame Laminate line, and exposed to chemicals in the spoiler & painting line. Potential Risk assessment resulted in categories of 11% extreme, 45% hard, 22% medium, and 22% medium. Risk control is proposed in the extreme category, namely the need for good design of traffic displays and vehicle substitution. In the hard category, it is proposed to increase discipline regarding SOP and APD in handling finished products, using cutting tools, handling flammable materials, handling Flame Lamenate machines. By proposing several treatment options for controlling both extreme and hard risks, automotive companies can reduce the risk of accidents, increase productivity, and create a safe work environment.